Seventy years of banking system in India: 1947 - 48 to 2016 - 17 - Bhasin, Niti (New Century, 2016)
India has a long and checkered history of financial intermediation, particularly in the commercial banking industry. Soon after Independence in 1947, the government of India followed a policy of social control of important financial institutions, which was followed by the takeover of the then Imperial Bank of India in 1956. In 1969, the government nationalised 14 major commercial banks and, in 1980, six more commercial banks were nationalised and brought under public ownership. Until the initiation of economic reforms in early 1990s, banking business in India was a near-monopoly by the government of India. As a result of state domination, until the early 1990s India's banking system was characterised by barriers to entry, control over pricing of financial assets, high transaction costs, and restrictions on movement of funds from one market segment to another. It was against this backdrop that wide-ranging banking sector reforms were introduced as an integral part of the economic reforms program. These reforms have paved the way for integration among various segments of the financial system. This book explains and examines, at length, the changes which have swept India's banking sector since Independence in 1947, with focus placed on the post-1991 period. [Subject: Banking &?Finance, Economic History, India Studies]